UV-activated persulfate oxidation and regeneration of NOM-Saturated granular activated carbon. (15th April 2015) - An, Dong; Westerhoff, Paul; Zheng, Mengxin; Wu, Mengyuan; Yang, Yu; Chiu, Chao-An
Abstract: A new method of ultraviolet light (UV) activated persulfate (PS) oxidation was investigated to regenerate granular activated carbon (GAC) in drinking water applications. The improvements in iodine and methylene blue numbers measured in the GAC after ultraviolet- (UV) activated persulfate suggested that the GAC preloaded with natural organic matter (NOM) was chemically regenerated. An experimental matrix for UV-activated persulfate regeneration included a range of persulfate doses and different UV wavelengths. Over 87% of the initial iodine number for GAC was restored under the optimum conditions, perfulfate dosage 60 g/L and UV exposure 1.75 × 10 4 mJ/cm 2 . The persulfate dosages had little effect on the recovery of the methylene blue number, which was approximately 65%. Persulfate activation at 185 nm was superior to activation at 254 nm. UV activation of persulfate in the presence of GAC produced acid, lowering the solution pH. Higher persulfate concentrations and UV exposure resulted in greater GAC regeneration. Typical organic and inorganic byproducts (e.g., benzene compounds and sulfate ions) were measured as a component of treated water quality safety. This study provides a proof-of-concept that can be used to optimize pilot-scale and full-scale UV-activated persulfate for regeneration of NOM-saturated GAC. Graphical abstract: Highlights: The technical feasibility of the regeneration for NOM-saturated GAC by UV-activated persulfate was investigated. GAC regeneration results were obtained under higher persulfate concentrations and 185 nm UV exposure dose. Both iodine and methylene blue numbers were measured as an indicator of GAC adsorption capacity.